The Impact of Egocentric Parenting Patterns on Children in Egocentric Novel by Sahid Muhammad - Salsabila, Salsabila Dwi Nurkhafifah; Nadhifah, Ainun; Kurniawan, Eva Dwi (JOYCED: Journal of Early Childhood Education, 2023)
This research was conducted to determine the impact of parents who have an egocentric nature and the parenting patterns used by children to see school counseling guidance on mothers and fathers in inappropriate and egocentric parenting patterns on children so that at least children can choose or take the results they want. always chosen by parents. The research method used is a narrative method using a qualitative approach. Then technique collection of relevant data with method library data collection, reading, recording and managing material study. Deep data analysis research This use data reduction is conclude the data so researcher know step in research. The results of this research are that there are still some parents who apply inappropriate parenting patterns, mothers and fathers with an egocentric nature will make children unable to make decisions because children are not allowed to choose. What children like. So it can be concluded that if the good and bad of a child's character is seen from the parenting style carried out by the mother and father at home, then it is necessary to provide direction in the form of parenting patterns with counseling guidance to the students' parents at school.